2021
DOI: 10.1371/journal.pone.0247062
|View full text |Cite
|
Sign up to set email alerts
|

“We are left with nothing to work with”; challenges of nurses working in the emergency unit at a secondary referral hospital: A descriptive qualitative study

Abstract: Introduction In recent times, there has been an increasing burden in traumatic, medical, and surgical emergency conditions, placing more emphasis on the need for quality emergency care. This study aimed to explore the challenges experienced by nurses working in the emergency unit of a secondary referral hospital. Methods The study used an exploratory qualitative research design with a constructivist approach and a grounded theory method. Data were collected through in-depth interviews lasting between 30 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This study's findings indicate that opportunities for skill acquisition and use positively affected quality of nursing work life, which is consistent with nurses' experiences of more challenging tasks and opportunities for diverse clinical roles in Ugandan private health facilities [38] . Nonetheless, the declining autonomy [23] , interference with nursing tasks [6] , non-nursing tasks [8] , [27] , inadequate staffing [19] , [21] [23] and high work demands [3] , [8] , [18] [20] found in previous studies were also found to negatively affect nursing QWL in the current study. Burnout emerged as an important quality of nursing work life concern in this study.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This study's findings indicate that opportunities for skill acquisition and use positively affected quality of nursing work life, which is consistent with nurses' experiences of more challenging tasks and opportunities for diverse clinical roles in Ugandan private health facilities [38] . Nonetheless, the declining autonomy [23] , interference with nursing tasks [6] , non-nursing tasks [8] , [27] , inadequate staffing [19] , [21] [23] and high work demands [3] , [8] , [18] [20] found in previous studies were also found to negatively affect nursing QWL in the current study. Burnout emerged as an important quality of nursing work life concern in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Work design encompasses the actual work nurses do and how the immediate work environment, such as autonomy at work, the workload and human resource availability; the time to do a job, non-nursing tasks and receiving assistance at work affect the well-being of nurses and organizational performance [5] . Evidence indicates that an excessive workload [3] , [8] , [18] [20] , lack of staff [19] , [21] [23] , long work hours [24] , [25] , weekend schedules [24] , emotional exhaustion [18] , [26] , conflicting priorities and diffuse responsibilities [6] and a lack of autonomy [23] negatively impact the quality of nursing work life. Nurses assumed various non-nursing roles at different levels, backstopping other health professionals to offer the best to their patients and their organization [8] , [27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from Afaya et al's study in 2021 revealed that the crowded nature of EDs is an important challenge in patient education and that nurses' fatigue often accompanies care provision. Given the insufficiency of nursing staff, the large number of patients, and stressful work environments, nurses cannot provide specialized training well, which affects the quality of emergency care (23). In 2018, Atakro et al reviewed the experiences of ED nurses, finding that the challenges of resources such as lack of space and insufficient nursing staff endanger the quality of emergency care and training.…”
Section: Environmental Challenges Including the Crowded Environment A...mentioning
confidence: 99%
“…Similarly, a study Afaya et al, (2021) aimed at exploring the challenges experienced by nurses working in the EW of a secondary referral hospital in Ghana, found overcrowding; understaffing; lack of emergency equipment; and inadequate managerial support as major issues confronting EW staff. The purpose of this qualitative study was to explore the challenges experienced by nurses practicing at the University of Cape Coast Hospital concerning their BLS resources availability and practices.…”
Section: Introductionmentioning
confidence: 99%